2020
DOI: 10.3390/nu12040989
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Contributes to Osteosarcopenic Adiposity via Inflammation and Immune Modulation: The Case for More Precise Nutritional Investigation

Abstract: Chronic stress and low-grade chronic inflammation (LGCI) are key underlying factors for many diseases, including bone and body composition impairments. Objectives of this narrative review were to examine the mechanisms by which chronic stress and LGCI may influence osteosarcopenic adiposity (OSA) syndrome, originally named as ostoesarcopenic obesity (OSO). We also examined the crucial nutrients presumed to be affected by or cause of stress and inflammation and compared/contrasted them to those of our prehistor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 124 publications
(162 reference statements)
1
89
0
Order By: Relevance
“…An interesting finding in this study showed, different from women, men with OSO had a significantly higher PBF% and a lower muscle mass compared with O and OO groups, but their BMI values are not increasing in OSO group. 33,36 In other words, OSO appears to be more associated with high-fat/low-muscle mass body composition types in men. This finding is also supported by a previous study, they found that senior males with OSO showed unfavorable body composition compared with their peers with SO, OO or O.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An interesting finding in this study showed, different from women, men with OSO had a significantly higher PBF% and a lower muscle mass compared with O and OO groups, but their BMI values are not increasing in OSO group. 33,36 In other words, OSO appears to be more associated with high-fat/low-muscle mass body composition types in men. This finding is also supported by a previous study, they found that senior males with OSO showed unfavorable body composition compared with their peers with SO, OO or O.…”
Section: Discussionmentioning
confidence: 97%
“…32 Also, a new concept of osteosarcopenic adiposity (OSA) has been implemented, it is suggested that OSO definition is not just overt overweight/obesity (BMI), special attention should also be paid to infiltrating fat in bone and redistributing fat in visceral area. 33 For example, the reduction of muscle satellite cells caused by myosteatosis and the infiltration of bone marrow adipocytes. 34,35 The incidence of OSO in this study is 10.2%, which is a little higher than a previous study in China (7.3%).…”
Section: Discussionmentioning
confidence: 99%
“…OSA refers to the simultaneous loss of bone mass and strength (osteopenia/osteoporosis), diminished skeletal muscle mass, strength and functionality (sarcopenia/dynapenia), and gain in adipose tissue (either as overt obesity, or as redistributed fat in abdominal/visceral area, or as infiltrated fat into bone and muscle) [ 1 , 2 , 3 , 4 ]. OSA has been studied across the world and associated with poor diet, various metabolic disorders and compromised functionality, including balance, walking speed and handgrip strength, in populations of different backgrounds, sex and age, as recently reviewed in [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another critical health aspect is the presence of low-grade chronic inflammation (LGCI) which might run undetected and unresolved for long periods, but which is increasingly recognized as a contributing factor to numerous comorbidities, including OSA [ 6 , 7 ]. In fact, the “cytokine storm” manifested in COVID-19 infection [ 8 ] has been suggested to be triggered or at least worsened by the presence of LGCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation